« L’Amazonie – victime des changements climatiques ? » - Sebastian Weissenberger; Delaine Sampaio da Silva (Confins)
The Amazon rainforest is one of most important ecosystems on earth and a biodiversity hotspot. Its future is however in peril due to the effects of climate change and human activities. Climate models predict a severe die-back of the Amazon forest by the end of this century, accompanied by the release of vast quantities of carbon actually stored in the vegetation. Deforestation is currently responsible for over one half of Brazil’s greenhouse gas emissions. Fighting deforestation is therefore Brazil’s most efficient way to reduce its emissions. This is however contrary to current development schemes in the Amazon region, and in particular large scale agricultural and cattle raising farms. However, Brazil has recently put policies in place in order to guarantee a greater protection of the Amazon environment. These policies are confronted with résistance from economic and political interests. International initiatives such as reduced emissions from deforestation and forest degradation (REDD), within the framework of a global climate treaty, can provide Financial and political incentives for conservation policies. It is essential that such initiatives take into account the socioeconomic situation of the Amazon region and be implemented in collaboration with the local populations in a perspective of social as well as ecological and economic development.